2002
DOI: 10.1152/japplphysiol.00688.2001
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of guinea pig trachealis during electrical field stimulation increases with age

Abstract: Our laboratory has previously shown that maturation of airway smooth muscle (ASM) contractility may play a role in the airway hyperresponsiveness displayed by juveniles of many species, including humans (Chitano P, Wang J, Cox CM, Stephens NL, and Murphy TM. J Appl Physiol 88: 1338-1345, 2000). ASM relaxation, which could also contribute to airway hyperresponsiveness, has neither been described nor quantified during maturation. Therefore, we studied ASM relaxation during and after electrical field stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 25 publications
4
34
0
Order By: Relevance
“…It is known that prostanoids exert on ASM both relaxing and contractile actions with PGE 2 and PGI 2 mainly acting as relaxing factors (23). Chitano et al (6) showed that whereas ASM from adult guinea pigs relaxes to the baseline level while the stimulation is ongoing, 1-wk ASM maintains the contractile state throughout the stimulation. In the presence of indomethacin, 1-wk ASM is able to spontaneous relax like adult muscle strips.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that prostanoids exert on ASM both relaxing and contractile actions with PGE 2 and PGI 2 mainly acting as relaxing factors (23). Chitano et al (6) showed that whereas ASM from adult guinea pigs relaxes to the baseline level while the stimulation is ongoing, 1-wk ASM maintains the contractile state throughout the stimulation. In the presence of indomethacin, 1-wk ASM is able to spontaneous relax like adult muscle strips.…”
Section: Discussionmentioning
confidence: 99%
“…In guinea-pigs, CHITANO and co-workers [10,21] have shown that isometric relaxation of electrically stimulated TSM is decreased in 1-week-old animals compared with 3-week and 3-month-old animals while calculated maximum shortening velocity extrapolated at zero-load is reduced in adults. These results suggest that increased velocity of shortening and decreased isometric relaxing capacity could contribute, at least in part, to the greater incidence of AHR reported in children and juvenile animals [8].…”
Section: Relaxation In Ahrmentioning
confidence: 99%
“…Thus, from a mechanical point of view, the electrically stimulated TSM of rats behaves like canine [24,25], porcine [26], mouse [27] or rabbit [28] TSM and differs from bronchial smooth muscle of humans [14] and TSM of guinea-pigs [10,29], which are both known to exhibit active resting tension. The present data clearly indicate that innate differences in airway responsiveness could not be attributed to differences in active resting tension level in the rat strains under study.…”
Section: Isotonic Relaxation In Fisher and Lewis Ratsmentioning
confidence: 99%
See 2 more Smart Citations